Developing agentic professionals through practice-based pedagogies. - Billett, Stephen (Australian Learning and Teaching Council, 2009)
Currently, in higher education institutions across the world, there is a growing interest in work-integrated learning. In particular, in courses preparing graduates for specific vocational outcomes, the interest has occurred in response to the need to prepare students who are ready and able to practice effectively in their professions on graduation. This Fellowship has enacted and appraised practices for effectively integrating students' learning experiences across university and practice settings to assist in realising the educational purposes of preparing graduates who are professionally adept and critical practitioners. The Fellowship's specific focus has been to identify how students can be prepared, supported and sustained as agentic learners in both their learning through experiences in practice settings and as effective professional practitioners. This goal has been addressed through engaging with and guiding five sets of academic staff in projects across four disciplines (Physiotherapy, Midwifery, Nursing, Human Services) in three universities (Griffith, Monash and Flinders). [Executive summary]